From waste to weapon: the potential of medicinal plant waste extracts for eco-friendly crop disease management - Jiang, Chang-Jie; Sun, Yao; Xu, Shijiao; Liu, Xinqiong; Xie, Xianzhi (Frontiers in Sustainable Food Systems, 2025)
The increasing challenge of managing crop diseases requires innovative and sustainable approaches. The current reliance on synthetic pesticides raises environmental concerns and contributes to the development of pesticide resistance. Therefore, exploration of alternative, eco-friendly biocontrol agents is crucial. In this article, we examine the underutilized potential of medicinal plant wastes (MPWs) as renewable and eco-friendly resources for the control of crop diseases. MPWs contain a significant portion of bioactive compounds with biopesticidal potential and represent a readily available and cost-effective source. Here, we review the recent findings on the efficacy of MPW extracts, discuss their mechanisms of action, and highlight their applications in crop protection. The contents presented herein emphasize the importance of MPW extracts as sustainable alternatives or complements to conventional synthetic pesticides and offer new possibilities for environmentally conscious strategies in crop disease management.